Siyerin hadislerle yeniden inşâsı (sahîhayn çerçevesinde ve sîret-i ibn hişâm ile karşılaştırmalı olarak) - Durmuş, Üzeyir (My University, 2016)
SİYERİN HADİSLERLE YENİDEN İNŞÂSI (SAHÎHAYN ÇERÇEVESİNDE VE SÎRET-İ İBN HİŞÂM İLE KARŞILAŞTIRMALI OLARAK) Siyer ilmi Hz. Peygamber'in hayatını anlatan ve bu yönüyle onu örnek alması gereken müslümanlar için oldukça önemli olan bir ilimdir. Ancak birçok siyer kitabında çok zayıf ve mevzû' rivayetlerin olması onları okuyanları yanlış bir peygamber algısına yönlendirebilmektedir. Bu nedenle siyerin sahîh rivâyetlerden oluşması büyük önem taşımaktadır. Bunun için de hadis rivayetlerinden faydalanmak ve siyer rivâyetlerini hadis ilminin tenkit usulleriyle değerlendirmek gerekmektedir. Bu tezde, hadis ilminin en sahîh iki kitabı olan İmam Buhârî ve İmam Müslim'in el-Câmiü's-sahîh'lerindeki siyer rivâyetleriyle bir metin inşâ edilmekte, inşâ edilen bu metin siyer ilminin en güvenilir eseri olan İbn Hişam'ın es-Sîretü'n-nebeviyye'si ile karşılaştırılmakta ve bu metnin İbn Hişâm'ın eserinin konu başlıklarını neredeyse tamamen içerdiği ortaya konulmaktadır. İçerik ve yöntem karşılaştırmalarıyla zenginleştirilen, yaklaşık 400 başlık ve bu başlıklar altında 1500 civarında hadis içeren ve siyer kitaplarından yapılan alıntılarla gelişmiş bir kronolojiye sahip kılınan bu çalışmayla siyerin hadislerle yeniden inşâsının mümkün olduğu ispat edilmekte ve siyerin hadis tasnîf türleri arasına eklenmesi teklif edilmektedir. Hadis, sîret, siyer, hadislerle siyer, sahih siyer

RECONSTRUCTION OF SIYAR WITH HADITHS (WITHIN THE FRAMEWORK OF SAHÎHAYN AND COMPARING WITH SIRA IBN HISHAM) Siyar science is a study which is about the life Prophet Mohammed (PBUH) and for all the Muslim believers should take him as their exemplars it becomes a very crucial discipline in religious studies. But in many siyar books there are very weak and wrong narratives referred to Prophet Mohammed which may cause believers to know the life-style and recommendations of the Prophet in a very unwanted way. Due to this concern, the construction of the sira out of the authentic hadiths is of the utmost significance. In order to bring about this construction, what should be done is to benefit from the hadiths and to assess the narrations through methods of criticism applied in the hadith science. In this thesis, a text is constructed with the endorsement of the narratives of prophet Muhammad (PBUH) authored in the soundest books of the science of Hadith calledal-Jami as-Sahih, which are written by Imam Bukhariand Imam Muslim, and the constructed text is analogically handled in comparison to the most reliable source of the life of prophet Muhammad (PBUH), entitled as-Sirat an-Nabawiyyah whose author is Ibn Hisham, and it is designated that approximately all the headings in the book of Ibn Hisham are covered in aforementioned text. In this piece of work there are 400 headlines under which there are approximately 1500 Hadiths. The text is enriched by comparing contents and methods of different siyar books by quotations and also a large chronological reference is given. By this way it is proved that it is possible to recreate Siyar by the help of Hadith and it is proposed that Siyar books should be classified as a subform of Hadith. Hadith, the Sira, siyar, siyar with Hadiths, the Authentic siyar
Keywords: Hadis; İslam dini